OPTIMALISASI PEMBIMBINGAN TUGAS AKHIR DIPLOMA IV TEKNIK LISTRIK BANDARA MELALUI SOSIALISASI PANDUAN AKADEMIK SESUAI KETENTUAN DIREKTORAT JENDERAL PENDIDIKAN TINGGI (DIKTI) - Fatonah, Feti; Desryanto, Nurhedhi; J, I Wayan; Kosasih, A.; Taryana, Taryana; K, Iwan; S, Rubby; Lamtiar, Suse; K, Zulina; Ismail, KGS. (MAJU : Indonesian Journal of Community Empowerment, 2025)
This Community Service Program (PKM) aims to enhance the competence and understanding of academic supervisors in guiding and supervising the final project writing of students in the Diploma IV Airport Electrical Engineering Program at the Indonesian Civil Aviation Polytechnic of Curug (PPIC). The background of this activity is based on the essential role of academic supervisors as guarantors of academic quality and the scientific integrity of students’ final projects, in accordance with the regulations of the Directorate General of Higher Education (DIKTI) as stipulated in the Ministry of Education and Culture Regulation (Permendikbud) No. 3 of 2020 concerning National Higher Education Standards. The main issues faced by the study program include the lack of uniformity in supervision guidelines, limited supervision time, and differing perceptions among lecturers regarding the implementation of academic guidelines. The activity was conducted through a one-day socialization and interactive discussion under the theme “Optimizing Final Project Supervision for Diploma IV Airport Electrical Engineering through the Socialization of Academic Guidelines in Accordance with DIKTI Regulations.” Participants included lecturers and laboratory staff from the study program, who received material presentations on supervision guidelines, principles of effective supervision, and the implementation of a structured supervision format. Evaluation was carried out through a post-activity questionnaire to assess the relevance and benefits of the program in improving supervision quality. The results show that this program is highly relevant and beneficial, providing clearer understanding of the application of DIKTI guidelines in the supervision process of final projects. This PKM activity successfully increased lecturers’ awareness of the importance of structured supervision, strengthened the implementation of the Tri Dharma of Higher Education in the aspects of community service and vocational lecturer competence development, and supported the improvement of both the quality and timeliness of student final project completion.